1994
DOI: 10.1007/bf00048321
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for somatic plantlet production in hybrid larch (Larix � leptoeuropaea): Part 1. Somatic embryo maturation

Abstract: Somatic embryogenesis was induced from full-sib immature zygotic embryos of hybrid larch (Larix × leptoeuropaea) that were collected at three different dates. Analysis of variance showed interaction between the collection date and the induction medium. The highest response (55%) was observed from embryos that were at the precotyledonary stage. Twelve media containing various concentrations of abscisic acid and sucrose were used to promote the development of 'high quality' mature somatic embryos that would unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 34 publications
(38 reference statements)
2
45
0
2
Order By: Relevance
“…Embryogenic cultures (ECs) were induced from immature zygotic embryos of the hybrid larch [11]. One cell line (69.18) was maintained in suspension culture in MSG medium supplemented with 1.46 g L -1 glutamine, 9 µM 2,4-D and 2.25 µM benzyladenine.…”
Section: Larch (Larix Leptoeuropaea Dengler)mentioning
confidence: 99%
“…Embryogenic cultures (ECs) were induced from immature zygotic embryos of the hybrid larch [11]. One cell line (69.18) was maintained in suspension culture in MSG medium supplemented with 1.46 g L -1 glutamine, 9 µM 2,4-D and 2.25 µM benzyladenine.…”
Section: Larch (Larix Leptoeuropaea Dengler)mentioning
confidence: 99%
“…Many attempts have been done in order to improve the initiation of embryogenic tissues in conifers. The effort focused mainly on testing of nutrient medium com-position and plant growth regulators (Ewald et al 1995, Hazubska-Przybyl andBojarczuk 2008), carbon sources ( Salajova and Salaj 2005), vitamins (Pullman et al 2006), medium salt composition (Lelu et al 1994, Becwar et al 1990, Miguel et al 2004, Kim et al 2009, Krajňáková et al 2008, polyamines effect (Nakagawa et al 2011) as well as environmental (Vookova and Kormutak 2009) and genetic effects (Cheliak and Klim·aszewska 1991, Niskanen et al 2004, Yildirim et al 2006) have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a large number of somatic embryos (from first, secondary and third generation callus line) at the cotyledonary stage was obtained if they were cultured with 20-60 µM ABA and 1 µM IBA for 4 weeks in dim light (25-30 µE m -2 s -1 ). Lelu et al (1994b) and Gutman et al (1996) reported that culture with 60 µM ABA results in proper development of somatic embryos of Larix × leptoeuropaea, and they are morphologically similar to zygotic embryos. Our results indicate that larch callus of line 7 (L. × leptoeuropaea 69.18) produced somatic embryos most efficiently (as compared to the other larch lines) if cultured with 60 µM ABA and 1 µM IBA, for 3-4 weeks.…”
Section: Maturation Of Somatic Embryosmentioning
confidence: 99%